STUDY OF THE PREVALENCE OF MENOPAUSAL DISORDERS AND AWARENESS OF THE POSSIBILITIES OF HORMONE THERAPY AMONG WOMEN OVER 45 YEARS OF AGE - Бибикова, Александра; Коваль, Ирина (SWorldJournal, 2020)
About 1/3 of a woman's life is spent in the menopausal period, which can manifest itself in various symptoms. To assess the prevalence of menopausal disorders and awareness of the possibilities of hormone therapy, 50 women over 45 years of age were inclu